2017
DOI: 10.1007/s11356-017-0555-4
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of excessive utilization of crude protein in ruminants ration: impact on environmental ecosystem and opportunities of supplementation of limiting amino acids—a review

Abstract: Protein quality plays a key role than quantity in growth, production, and reproduction of ruminants. Application of high concentration of dietary crude protein (CP) did not balance the proportion of these limiting amino acids (AA) at duodenal digesta of high producing dairy cow. Thus, dietary supplementation of rumen-protected AA is recommended to sustain the physiological, productive, and reproductive performance of ruminants. Poor metabolism of high CP diets in rumen excretes excessive nitrogen (N) through u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 75 publications
0
24
1
Order By: Relevance
“…In addition, compared with feed protein, MCP is an excellent source for milk protein production in terms of amino acid contents [4]. Meanwhile, a better balance and utilization of ruminal degradable and undegradable protein can increase metabolizable protein and reduce nitrogen excretion in urine and feces [5]. Therefore, the improvement of ruminal microbial protein synthesis (MPS) not only benefits milk protein production, but also benefits nitrogen utilization efficiency, which avoids excessive emission of nitrogen to the environment [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, compared with feed protein, MCP is an excellent source for milk protein production in terms of amino acid contents [4]. Meanwhile, a better balance and utilization of ruminal degradable and undegradable protein can increase metabolizable protein and reduce nitrogen excretion in urine and feces [5]. Therefore, the improvement of ruminal microbial protein synthesis (MPS) not only benefits milk protein production, but also benefits nitrogen utilization efficiency, which avoids excessive emission of nitrogen to the environment [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, it is difficult for essential AAs to maintain dynamic balance when lipid metabolism is disordered. Although the concentration of AAs in plasma can be dynamically maintained in a balance by the release of endogenous proteins and the utilization of tissues [29,30], it is different for essential AAs because they cannot be synthesized in the body. Our results indicated that the mean blood levels of Val, Phe, Trp, His, and Met were changed in hyperlipidemic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…NH 3 is other gas to be monitored due to surface water pollution, soil eutrophication, and acidification [53]. Kodu et al [42] elaborated GPN functionalized with vanadium pentoxide (V 2 O 5 ) using laser ablation technique for the production of a highly sensitive NH 3 sensor.…”
Section: Chemical-properties Sensorsmentioning
confidence: 99%